Infrared camera based thermometry for quality assurance of superficial hyperthermia applicators - Müller, Johannes; Hartmann, Josefin; Bert, Christoph (Physics in Medicine and Biology, 2016)
The purpose of this work was to provide a feasible and easy to apply phantom-based quality assurance (QA) procedure for superficial hyperthermia (SHT) applicators by means of infrared (IR) thermography. The VarioCAM hr head (InfraTec, Dresden, Germany) was used to investigate the SA-812, the SA-510 and the SA-308 applicators (all: Pyrexar Medical, Salt Lake City, UT, USA). Probe referencing and thermal equilibrium procedures were applied to determine the emissivity of the muscle-equivalent agar phantom. Firstly, the disturbing potential of thermal conduction on the temperature distribution inside the phantom was analyzed through measurements after various heating times (5-50 min). Next, the influence of the temperature of the water bolus between the SA-812 applicator and the phantom's surface was evaluated by varying its temperature. The results are presented in terms of characteristic values (extremal temperatures, percentiles and effective field sizes (EFS)) and temperature-area-histograms (TAH). Lastly, spiral antenna applicators were compared by the introduced characteristics. The emissivity of the used phantom was found to be ? = 0.91 ± 0.03, the results of both methods coincided. The influence of thermal conduction with regard to heating time was smaller than expected; the EFS of the SA-812 applicator had a size of (68.6 ± 6.7) cm(2), averaged group variances were ±3.0 cm(2). The TAHs show that the influence of the water bolus is mostly limited to depths of <3 cm, yet it can greatly enhance or reduce heat generation in this regime: at a depth of 1 cm, measured maximal temperature rises were 14.5 °C for T Bolus = 30 °C and 8.6 °C for T Bolus = 21 °C, respectively. The EFS was increased, too. The three spiral antenna applicators generated similar heat distributions. Generally, the procedure proved to yield informative insights into applicator characteristics, thus making the application of an IR camera a very useful tool in SHT technical QA.
EVALuna2:18343